1990
DOI: 10.1111/j.1365-2362.1990.tb02262.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of simvastatin on plasma lipoproteins and cholesterol homeostasis in patients with heterozygous familial hypercholesterolaemia

Abstract: We have examined the influence of simvastatin, a competitive inhibitor of 3-hydroxy-3-methyl glutaryl coenzyme A reductase on plasma concentrations of lipids and lipoproteins, the rates of cholesterol biosynthesis and degradation of 125T-labelled LDL by freshly isolated mononuclear leucocytes and the 24 h urinary excretion of mevalonic acid in patients with heterozygous familial hypercholesterolaemia. Patients were treated with progressively increasing doses of simvastatin (20,40, and 80 mg day-') taken in a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 28 publications
5
10
0
Order By: Relevance
“…Therefore, 44 W anner/Lubrich-Birkner/Summ/W leland/ Simvastatin in CAPD Patients Schollmeyer this group of patients, theoretically prone to muscular dam age and side effects, were monitored closely in the present study to detect complications early. Hagemenas et al [30] showed that 100 mg of M C simvastatin given in a single dose to healthy subjects was completely cleared from the circula tion after 12 h. Comparable results were obtained in our patients since no inhibitory activity of simvastatin could be detected in plasma 12 h after simvastatin administration. This would confirm the lack of clinical side effects and laboratory abnormalities.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, 44 W anner/Lubrich-Birkner/Summ/W leland/ Simvastatin in CAPD Patients Schollmeyer this group of patients, theoretically prone to muscular dam age and side effects, were monitored closely in the present study to detect complications early. Hagemenas et al [30] showed that 100 mg of M C simvastatin given in a single dose to healthy subjects was completely cleared from the circula tion after 12 h. Comparable results were obtained in our patients since no inhibitory activity of simvastatin could be detected in plasma 12 h after simvastatin administration. This would confirm the lack of clinical side effects and laboratory abnormalities.…”
Section: Discussionsupporting
confidence: 68%
“…It has also been observed that statins up-regulate hepatic LDLR expression and inhibition of HMG-CoA reductase results in a secondary increase in LDLR activity (3,24,25). Therefore, it is possible that statin therapy might affect the results even though peripheral lymphocytes, and not hepatocytes, were used in this study (26,27). There have been some conflicting reports about the relationship between statin therapy and LDLR activity of lymphocytes (12).…”
Section: Discussionmentioning
confidence: 97%
“…The hypocholesterolemic effect of lovastatin administered against the background of obsidan depends on its diurnal dose. There are diverse published data on the effect of lovastatin on the rate of Ch synthesis in peripheral blood lymphocytes [7,8,13]. We showed that this effect depends on the diurnal dose of the preparation and on the degree of the drop of total serum Ch.…”
Section: Methodsmentioning
confidence: 79%
“…These results indicate the existence of an inverse relationship between the rate of Ch synthesis in lymphocytes and the level of serum Ch. The synthesis of Ch in lymphocytes depends on the concentration of Ch in the cell, i.e., it is regulated by feedback [5,8]. The elevation of the total Ch level observed after 6 months of lovastatin treatment was accompanied by a decreased rate of Ch synthesis in the lymphocytes.…”
Section: Methodsmentioning
confidence: 99%